Slow reading in children with anisometropic amblyopia is associated with fixation instability and increased saccades - Kelly, Krista R (J AAPOS, 2017)
BACKGROUND: Previous studies show slow reading in strabismic amblyopia. We recently identified amblyopia, not strabismus, as the key factor in slow reading in children. No studies have focused on reading in amblyopic children without strabismus. We examined reading in anisometropic children and evaluated whether slow reading was associated with ocular motor dysfunction in children with amblyopia. METHODS: Anisometropic children (7–12 years) with or without amblyopia were compared to age-similar normal controls. Children silently read a grade-appropriate paragraph during binocular viewing. Reading rate (words/min), number of forward and regressive saccades (per 100 words) and fixation duration were recorded with the ReadAlyzer. Binocular fixation instability was also evaluated (EyeLink 1000). RESULTS: Amblyopic anisometropic children read more slowly (n = 25; mean with standard deviation, 149 ± 42 words/min) than nonamblyopic anisometropic children (n = 15; 196 ± 80 words/min; P = 0.024) and controls (n = 25; 191 ± 65 words/min; P = 0.020). Nonamblyopic anisometropic children read at a comparable rate to controls (P = 0.81). Slow reading in amblyopic anisometropic children was correlated with increased forward saccades (r = −0.84, P < 0.001), increased regressive saccades (r = −0.85, P < 0.001), and fellow eye instability during binocular viewing (r = −0.52, P = 0.019). CONCLUSIONS: Slow reading in school-age children with anisometropic amblyopia is related to increased frequency of saccades and fixation instability of the fellow eye. Further research should consider the effects of slower reading on academic performance.